2016
DOI: 10.1021/acs.energyfuels.6b00132
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Catalytic Pyrolysis of Benzoic Acid as a Coal-Based Model Compound

Abstract: Benzoic acid (C 6 H 5 COOH) is selected as a coal-based model compound, and its catalytic pyrolysis mechanisms on ZnO, γ-Al 2 O 3 , CaO, and MgO catalysts are studied using density functional theory (DFT) compared to the non-catalytic pyrolysis mechanism. DFT calculation shows that the pyrolysis process of C 6 H 5 COOH in the gas phase occurs via the direct decarboxylation pathway (C 6 H 5 COOH → C 6 H 6 + CO 2 ) or the stepwise decarboxylation pathway (C 6 H 5 COOH → C 6 H 6 COO → C 6 H 6 + CO 2 ). For C 6 H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 61 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…The energy barriers of pathways 1 and 2 are similar, which are far lower than that of pathway 3. Therefore, pathways 1 and 2 for C6H5COOH pyrolysis are possible, which is similar with our previous study [20]. The potential energy diagrams of C6H5COOH pyrolysis and the corresponding initial states (IS), transition states (TS) and final states (FS) are shown in Figure 2.…”
Section: C6h5cooh Pyrolysissupporting
confidence: 87%
See 3 more Smart Citations
“…The energy barriers of pathways 1 and 2 are similar, which are far lower than that of pathway 3. Therefore, pathways 1 and 2 for C6H5COOH pyrolysis are possible, which is similar with our previous study [20]. The potential energy diagrams of C6H5COOH pyrolysis and the corresponding initial states (IS), transition states (TS) and final states (FS) are shown in Figure 2.…”
Section: C6h5cooh Pyrolysissupporting
confidence: 87%
“…The potential energy diagrams and corresponding IS, TS and FS geometrical structures of C6H5COOH catalytic pyrolysis on Co3O4(110)-B surface are shown in Figure 4. It is demonstrated that the energetically preferred pathway of C6H5COOH catalytic pyrolysis on Co3O4(110)-B is C6H5COOH(g) →*C6H5COO + *H →*C6H5 + *CO2 +*H→*CO2+*C6H6 →CO2(g) + C6H6(g), which is similar with C6H5COOH pyrolysis on MgO, CaO and γ-Al2O3 surfaces [20]. The highest energy barrier (2.28 eV) on Co3O4(110)-B surface is smaller than that of C6H5COOH pyrolysis without a catalyst (2.78 and 2.89 eV).…”
Section: Catalytic Pyrolysismentioning
confidence: 76%
See 2 more Smart Citations
“…According to the current prevailing opinion, 9,24,39 the decarboxylation reaction during pyrolysis produces CO 2 . Wang et al 40 studied the decarboxylation mechanism of benzoic acid and proposed three possible pathways for decarboxylation: direct decarboxylation, stepwise decarboxylation, and a stepwise radical process. According to the results of Wang's calculations, the energy barrier of the direct decarboxylation (246 kJ mol À1 ) and stepwise decarboxylation (245 kJ mol À1 ) were much lower than that of the stepwise radical process (470 kJ mol À1 ).…”
Section: Design Of the Possible Reaction Pathsmentioning
confidence: 99%